Epilepsy in children with cerebral palsy - Hundozi-Hysenaj, Hajrie; Boshnjaku-Dallku, Iliriana (Journal of Pediatric Neurology, 2008)
Cerebral palsy (CP) is often associated with epilepsy. We sought to determine the frequency with which epilepsy is associated with CP and to define the relationship in terms of gender, etiology, pathophysiology, and topographical parameters. This was a retrospective analysis of children with CP treated at the University Clinical Centre of Kosova (UCCK) in Prishtina, over a 5-year period, 2000–2005. A total of 154 children (aged 7–15 years) with CP, treated at the UCCK were enrolled. CP was associated with epilepsy in 63 cases (40.9%), 29 (46.0%) of which had spastic quadriparetic CP; 17 (27.0%), diplegic CP; and 15 (23.8%), hemiparetic CP. For the quadriparetic children, there was no significant difference in the number associated with epilepsy between the genders (female, 45.2%; male, 46.9%). Epilepsy was frequently associated with CP, with the spastic quadriparetic group being most affected. There was no large difference in the number associated with epilepsy between the right and left hemiparetic CP cases. Tonic-clonic epilepsy was more frequently associated with hemiparetic CP, whereas partial-type epilepsy was more often associated with quadriparetic CP.
Keywords: Cerebral palsy; epilepsy